Understanding Zhongyong Using a Zhongyong Approach: Re-examining the Non-linear Relationship Between Creativity and the Confucian Doctrine of the Mean - Gao, Ruixiang; Huang, Shiqi; Yao, Yujie; Liu, Xiaoqin; Zhou, Yujun; Zhang, Shijia; Cai, Shaohua; Zuo, Huang; Zhan, Zehui; Mo, Lei (Frontiers in Psychology, 2022)
Previous studies on the relationship between zhongyong and creativity have not reached consistent results. Through review of literature, we assume it is because zhongyong has both a positive side that promotes creativity and a negative side that inhibits creativity, for that every coin has two sides is exactly one of the core concepts of zhongyong in traditional Chinese culture. In addition, as too much of a good thing is as bad as too little, we assume that the negative side is an excessive form of zhongyong. To testify our assumption, we conduct two empirical studies examining the relationship between positive and negative zhongyong and creativity (creative personality, divergent thinking, and convergent thinking). Moreover, in an effort to avoid the effect of social desirability, Study 2 for the first time adopt an implicit associative test to measure zhongyong. The results converged demonstrate an interaction between positive zhongyong and negative zhongyong, which can be interpreted as that only moderate level of zhongyong is beneficial to creativity while deficiency or excess is harmful. We discuss the implications for clarifying the nonlinear relationship between things with a zhongyong approach, and suggest to re-recognize the creativity of Chinese culture from a neutral and objective outlook. This paper contributes to provide a comprehensive understanding of zhongyong as well as clear insights into creativity from an in-depth cultural perspective.